Reflections about a pedagogical model as an orientation frame for teaching practices - Klimenko, Olena (Pensando Psicología, 2010)
From the human being’s socializing function (but above all humanizing) point of view, education plays a leading role. In order to fulfill the objective of man’s evolution in its humanizing aspect, searching an integral development of society members in knowledge, being, practice and coexisting dimensions, education emerges as an scholar phenomena in a more strict sense, which represents an organized process, consciously thought, planned, designed and implemented inside educative institutions. The article presents some reflections about the role constitutive elements, such as pedagogical model, curriculum and teaching practice within the configuration of the teaching as a contextualized cultural process. An approach to the relationship of mutual interdependence amog them is pretended in order to understand complexity of the determinants teaching labor has.